1994
DOI: 10.1177/104063879400600319
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelothrix Rhusiopathiae Infection in an Emu (Dromaius Novaehollandiae)

Abstract: The emu (Dromaius novaehollandiae) is a large flightless bird native to Australia. It belongs to the ratite group, which also includes ostriches, rheas, and cassowaries. The emu is reared commercially for its meat, oil, and skin; the skin is made into a high quality leather used in the manufacture of boots, handbags, etc. Erysipelothrix rhusiopathiae infection occurs widely in nature. In its septicemic form, the disease is commonly designated as erysipelas. It has most frequently been reported in pigs, but nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Clostridium difficile was probably responsible for the liver lesions. No other bacteria, such as C. perfringens, C. sordelli, Salmonella or Campylobacter, which have been associated with hepatitis in ratites, especially ostriches, were isolated from the liver of the ostrich chick (Post et al, 1991;Shivaprasad, 1993;Morgan et al, 1994;Vanhooser & Welsh, 1995;Poonacha & Donahue, 1997). No viruses were isolated from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficile was probably responsible for the liver lesions. No other bacteria, such as C. perfringens, C. sordelli, Salmonella or Campylobacter, which have been associated with hepatitis in ratites, especially ostriches, were isolated from the liver of the ostrich chick (Post et al, 1991;Shivaprasad, 1993;Morgan et al, 1994;Vanhooser & Welsh, 1995;Poonacha & Donahue, 1997). No viruses were isolated from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although Erysipelothrix infection in the wild birds is sporadic, some massive outbreaks have been reported in Eared Grebes of the Great Salt Lake (Jensen and Cotter, 1976). Free ranging wild and captive birds such as racing pigeons (Cousquer, 2005), quails (Mutalib et al, 1995), emus (Swan and Lindsey, 1998;Morgan et al, 2011), pheasants (Milne et al, 1997;Hennig et al, 2006), chukar partridge (Pettit et al, 1976), malleefowl (Blyde and Woods, 1999), parrots (Livingston et al, 2013), chukars (Butcher and Panigrahy, 1985), Hawaiian crow (Work et al, 1999), blue penguin (Boerner et al, 2004), endangered kakapo (Gartrell et al, 2005), laughing kookaburra (Opriessnig et al, 2005), takahe, kiwi, and black stilts (Alley and Gartrell, 2019) showed infections with E. rhusiopathiae.…”
Section: Figure 1 Different Virulence Factors Of Erysipelothrix Rhusi...mentioning
confidence: 99%
“…The organism is distributed worldwide and has been isolated from many species of wild and domestic mammals and birds, as well as from reptiles, amphibians and fish (Shuman 1971; Reboli and Farrar 1992). Diseases of economic importance in animals include: swine erysipelas, which presents as skin lesions, acute septicaemia and chronic arthritis; polyarthritis, commonly seen in sheep and lambs (Conklin and Steele 1979); and erysipelas of farmed turkeys, chickens and emus (Blackmore and Gallagher 1964; Morgan et al . 1994).…”
Section: Introductionmentioning
confidence: 99%